Influence of Financial Leverage, Corporate Size, and Capital Intensity on Profitability of Listed Food Industry Firms in Muscat Stock Exchange, Oman - Kollipara, Vamsi Prasad; Podili, Venkateswararao (Journal of Ecohumanism, 2025)
The objective of this study is to examine the effect of financial leverage, size of the firm and capital intensity on the profitability of the listed firms in the food industry on Muscat Stock Exchange (MSX) in the Sultanate of Oman. The goal of this research is to try to gain some insight into the way these three variables affect the performance of these companies financially. The Financial Leverage indicates the ratio of total debt to equity, and reveals to what extent firms use debt to finance their operations. Size of the corporation, measured by total assets, refers to the level of operation and the resulting economies of scale. Capital intensity reflects the extent of investment in long-term assets, measured as the ratio of fixed assets to total assets. This research analyzes the financial statements of a sample of 11 public food industry firms listed on the MSE for a five-year span based on panel data analysis. To assess profitability, we use return on assets (ROA) as performance indicator. Financial leverage has a mixed effect on profitability, and results indicate that high leverage potentially increases financial risk and interest obligations, which reduce profitability. In contrast, more substantial enterprises generally prosper better owing to economies of scale, greater market presence, and improved resource access. The capital intensity is positively correlated with profitability, asset-heavy constitutes high levels of fixed asset investment, can enhance the production efficiency and competitive advantage. The findings provide useful guidance for food sector corporate managers and investors/analysts as to the strategic importance of financial management in achieving the optimal capital structure to maximize profit. The results can also guide policymakers to create a conducive environment for the food sector in Oman.